Effect of Aspect Ratio on Natural Convection in a Porous Wavy Cavity - Cheong, Huey Tyng; Sivasankaran, Sivanandam; Bhuvaneswari, Marimuthu (Springer, 2018)
The present study analyzes natural convective flow and heat transfer in a wavy cavity saturated with porous medium. The sidewalls of the cavity are maintained at constant temperatures where higher temperature is applied on the vertical left wall while the wavy right wall is cooled at a lower temperature. The remaining top and bottom walls are taken to be adiabatic. The Darcy model is adopted for the fluid flow through the porous medium. The governing equations and boundary conditions are solved using the finite difference method over a range of cavity aspect ratios, wavy wall amplitudes, number of undulations and Darcy–Rayleigh numbers. The waviness of the cavity enhances the heat transfer inside the cavity, and the heat transfer rate is more enhanced when the aspect ratio of the cavity is close to 1. The study is applicable to the design of solar heating systems and geothermal reservoirs.